Hubungan Gaya Pengasuhan Orang Tua dengan Kemampuan Berpikir Kreatif Anak Usia 4-5 Tahun di TPA Mitfahul Jannah - Nurul Aini; Esperansa Mile; Safira Darmayanti; Fitri Adoe (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2025)
This research is motivated by the relationship between parenting styles and children's creative thinking abilities, especially in TPA Miftahul Jannah. The purpose of this study is to identify the parenting styles of children's parents with children's creative thinking abilities in TPA. This study uses quantitative methods with correlational design. Data were collected through observation, interview, data collection and documentation techniques, while teachers act as the main participants in this study. The results of the study indicate that parenting styles greatly influence children's creative thinking abilities. Parenting styles are a pattern or way parents educate, guide, and interact with children, which includes how they set rules, provide affection, and control children's behavior. In addition, teachers and caregivers at TPA also have an important role as parents of both children when they are in childcare. Teachers and caregivers at TPA Miftahul Jannah play an active role in caring for and educating children from toddler age to childhood. Parenting styles can improve children's creative thinking abilities. Through this approach, children can think creatively and imaginatively.